Penerapan Think Pair Share Terintegrasi TRI NGA (Ngerti, Ngrasa, Nglakoni) melalui Pembelajaran Seni Tari Kelas 1 SDN Kecis - Nuri Finaryanti; Moh Rusnoto Susanto; Rahimah Rahimah; Yuli Ernawati; Suwardi Suwardi; Diyah Novi Rahayu; Rohman Rohman; Mela Dina Arumsari; Arifah Suryaningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Dance art demands practice from students, but all this time teachers do not present dance art lessons by giving examples but only using the guides contained in the book package so students have difficulty in developing dance talent. The aim of this study is to enhance the creativity of students in various aspects of dance art learning. In order to this goal, the author used the integrated Think Pair Share method of TRI NGA. Based on the results of the study, 65% of first-class students entered the category that meets the standards, while the other 35% have already exceeded the standard, with an average value of improvement in creativity reaching 84. According to the research results the method used has been stated successfully improved the creativity of dance art students in 1st grade in SD Negeri Kecis.